2020
DOI: 10.5114/aoms.2020.98635
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 protein as a new biomarker in patientswith precapillary pulmonary hypertension

Abstract: Introduction: Non-invasive tests that may improve clinical evaluation of pulmonary hypertension (PH) are needed. The purpose of this study was to assess the role of soluble ST2 (sST2) in patients with PH. Material and methods: A total of 57 patients with chronic thromboembolic PH and 43 patients with idiopathic arterial PH were enrolled in this study. All patients were evaluated for World Health Organization (WHO) functional class (FC), N-terminal prohormone B-type natriuretic peptide (NT-proBNP), troponin T (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
4
2
0
Order By: Relevance
“…The important prognostic role of sST2 has already been established in several previous studies [10,12,27,29,45] and our results just further ascertained that sST2 is an important predictor of mortality, both in-hospital and at 1-month follow-up. Beside the fact that sST2 was significantly associated with short-term adverse outcomes in patients with acute HF enrolled in our study, we can also consider it as a useful tool for patients' follow-up, whether they are presenting stable or decompensated HF.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The important prognostic role of sST2 has already been established in several previous studies [10,12,27,29,45] and our results just further ascertained that sST2 is an important predictor of mortality, both in-hospital and at 1-month follow-up. Beside the fact that sST2 was significantly associated with short-term adverse outcomes in patients with acute HF enrolled in our study, we can also consider it as a useful tool for patients' follow-up, whether they are presenting stable or decompensated HF.…”
Section: Discussionsupporting
confidence: 87%
“…Basically, this confirms the utility of sST2 in detecting even isolated RV dysfunction, in the absence of echocardiographic aspects suggestive for LV systolic or diastolic dysfunction. Correspondingly, the involvement of sST2 in the functioning of the RV was also observed by Shah et al, who identified a correlation between high serum sST2 and an impaired RV systolic function expressed as diminished RV fractional area change [25], while another study highlighted the increased sST2 in patients with chronic thromboembolic or idiopathic pulmonary hypertension [29].…”
Section: Discussionsupporting
confidence: 56%
“…Particular attention should be paid to the association between sST2 and available right heart catheterization data. Positive correlations in this regard have already been described by Banaszkiewicz et al [ 37 , 38 ], who examined various subgroupings of PH for this association specifically. In our study, post-capillary PH patients showed a significant difference in terms of serum sST2 concentration in contrast to the patients without PH.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, in patients with heart failure, sST2 level above 35 ng/mL was linked to a higher risk of adverse events (defined as hospitalization or death in one year), compared to patients with sST2 levels below this value [ 28 , 29 , 30 ]. In patients with right heart failure due to PH, elevated sST2 concentrations were associated with right ventricular remodeling [ 14 ] and correlated both with biochemical parameters such as NT-proBNP or TnT and hemodynamic parameters [ 17 , 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%